BUSINESS PROCESS REENGINEERING IN THE BUSINESS PROCESS OF HAJJ AND UMRAH REGISTRATION SERVICES (CASE STUDY: MINISTRY OF RELIGION IN BALIKPAPAN CITY) - Ridha Auliya; I Putu Deny A.S. Prabowo (Airlangga Journal of Innovation Management, 2021)
The Ministry of Religion of the Republic of Indonesia is the Ministry within the Indonesian Government in charge of religious affairs. The Ministry of Religion in Balikpapan can serve in the fields of Education, Marriage, Waqf, Consultants on Household Issues, Mosque Construction, Hajj and others. The Ministry of Religion in the Field of Hajj and Umrah (PHU) Administrators as community organizers and facilitators who of course must behave professionally in serving, accompanying and assisting everything that is needed and prepared by prospective pilgrims before departure until returning to worship. Hajj and Umrah organizers as institutions within the ministry of religion certainly need to fulfill the demands of providing guidance. In this practical work, the special task carried out at the Ministry of Religion of the City of Balikpapan is to carry out Business Process Reengineering in the business process for Hajj registration services during the COVID-19 pandemic, so that the business process becomes more effective and efficient. Preparation of a Business Process with a Business Process Reengineering by providing additional activities and reducing activities. The addition of this activity for prospective pilgrims is proposed to first check the haj registration information on the kemenag.go.id website or asramahajibalikpapan.co.id. The information on the website is complete for community needs. So with the prospective pilgrims who can check Hajj registration information online, it can eliminate misunderstandings and the quality of service provided by the Ministry of Religion is already very good.